HUBUNGAN ANTARA MEMORI DENGAN KUALITAS HIDUP LANSIA DI DESA CILALUNG TANGERANG SELATAN - Khaerani Salsabila (2023)
Elderly people in Indonesia have increased from 18 million people (7.56%) in 2010, to 25.9 million people (9.7%) in 2019, and are expected to continue to increase in 2035 to 48, 2 million people (15.77%). The elderly will experience changes both physically and psychologically, physical changes usually experience a decrease starting from the cellular level to the entire organ system of the elderly. Research Objectives : To determine the relationship between memory and quality of life in the elderly. Research Methods: This study used a cross sectional study method. With memory measurement parameters, namely the Mini Mental State Examination (MMSE) and the parameters of the quality of life of the World Health Organization Quality of Life Brief Version (WHOQOL-BREF). Research Results: The results in this study found a relationship between memory and the quality of life of the elderly. With the results that experienced mild cognitive impairment was the largest number, namely with a total of 43 samples (39.1%) and good quality of life being the largest number because there were 40 samples (36.4%). Based on the results of statistical tests that have been tested using Spearman's rho, the p-value is 0.000 or p-value <0.005. Conclusion : This indicates that there is a relationship between memory and the quality of life of the elderly in Cilalug Village, South Tangerang, with a strong level category